Concurrent Diagnosis of Chronic Myeloid Leukemia and Follicular Lymphoma: An Unreported Presentation - Amy G. Starr; Sushma R. Jonna; Joeffrey J. Chahine; Bhaskar V. Kallakury; Chaitra S. Ujjani (Case Reports in Hematology)
Lymphadenopathy in chronic myeloid leukemia (CML) is usually due to extramedullary involvement with accelerated or blast phases of the disease. The occurrence of non-Hodgkin lymphoma (NHL) as a synchronous malignancy with CML is rare. We report a case of a 73-year-old male who presented with dyspnea and right-sided lower extremity edema in the setting of leukocytosis. Bone marrow evaluation indicated a chronic phase chronic myeloid leukemia (CML), confirmed by molecular testing. Imaging of the chest for persistent dyspnea revealed supraclavicular and mediastinal lymphadenopathy. Biopsy of the cervical node showed expanded lymphoid follicles with atypical germinal centers that were positive for CD10, BCL-2, and BCL-6, consistent with follicular lymphoma (FL). Nodal PCR demonstrated clonal IGH and IGK gene rearrangements, and FISH analysis was positive for IGH-BCL-2 fusion. Together, these tests supported the diagnosis of FL. Additionally, the lymph node showed paracortical expansion by maturing pan-hematopoietic elements, no blastic groups, and positive RT-PCR analysis for BCR-ABL1, indicating concomitant involvement by chronic phase-CML. To our knowledge, this is the first reported case of a patient with a concurrent diagnosis of CML and FL.